The Scholar and the Struggle : Lawrence Reddick's Crusade for Black History and Black Power - Varel, David A. (Book collections on Project MUSE., 2020)
"Lawrence Reddick (1910-1995) was among the most notable African American intellectuals of his generation. The second curator of the Schomburg Library and a University of Chicago PhD, Reddick helped spearhead Carter Woodson's black history movement in the 1930s, guide the Double Victory campaign during World War II, lead the Southern Christian Leadership Conference during the Cold War, mentor Martin Luther King Jr. throughout his entire public life, direct the Opportunities Industrialization Center Institute during the 1960s, and forcefully confront institutional racism within academia during the Black Power era. A lifelong Pan-Africanist, Reddick also fought for decolonization and black self-determination alongside Kwame Nkrumah, Nnamdi Azikiwe, Leopold Senghor, and W.E.B. Du Bois. Beyond participating in such struggles, Reddick documented and interpreted them for black and white publics alike"--